Analysis of Wastewater Management Systems at Bhayangkara Hospital, Palu - Siti Fatimahi; Miswan; Nur Rismawati (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2021)
This study aims to determine the wastewater management system at Bhayangkara Hospital, Palu. In carrying out their activities, hospitals produce liquid waste that can interfere with health. If not handled properly, it will cause harm to society and the environment. The research results at Bhanyangkara Hospital in Palu show that the wastewater management system already has many filters and other control tanks. A cover has accompanied each tub, channeled through an open channel, closed channel, the building is watertight, and the water flows smoothly. , already has a Flow Meter device but does not have a fat catcher, especially in the nutrition room, liquid waste in the Laboratory room at the third party to PT. Tenang Jaya Sejahtera until its destruction, the Radiology room has used the CR System, so there is no wastewater because it has used the tool, carries out primary and secondary treatment and supplies tools for treating liquid waste are still not available such as daily pH tools, pH tools handy for measuring the level of acidity/base of a liquid and besides that for the Flow Meter tool is readily available. Suggestions are expected that this study's results are used as input and become useful information, especially for Bhayangkara Hospital in Palu and the people living around Bhayangkara Hospital in Palu to know the impact of wastewater management.